1993
DOI: 10.2355/isijinternational.33.1049
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study on MnO Behavior in MgO-saturated Slag Containing FeO.

Abstract: Pohang,In order to understand the behavior of manganese oxide in smelting reduction process, the manganese equilibrium between ironmaking slag containing FeOand silver melt was investigated over the temperature range of 1 400-1 500'C. The oxygen partial pressure was controlled by COICO, ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…When comparing to earlier literature data [22,26,27], the calculated values of manganese distribution coefficient between copper alloy and slag appear to be much lower in this study. Jung et al [26] studied the manganese distribution between Cu alloy and CaO-SiO 2 -Al 2 O 3 (13%)-MnO(5%)-MgO(17%) slag at 1500 • C and at oxygen partial pressure 2.71 × 10 −12 atm. Eom et al [27] investigated the manganese distribution between copper alloy and CaO-SiO 2 -Al 2 O 3 (14.7%)-MnO(7.5%) slag at 1500 • C and at oxygen partial pressure 2.75 × 10 −10 atm.…”
Section: Distributions Of Metals Between Copper Alloy and Slagsupporting
confidence: 60%
See 1 more Smart Citation
“…When comparing to earlier literature data [22,26,27], the calculated values of manganese distribution coefficient between copper alloy and slag appear to be much lower in this study. Jung et al [26] studied the manganese distribution between Cu alloy and CaO-SiO 2 -Al 2 O 3 (13%)-MnO(5%)-MgO(17%) slag at 1500 • C and at oxygen partial pressure 2.71 × 10 −12 atm. Eom et al [27] investigated the manganese distribution between copper alloy and CaO-SiO 2 -Al 2 O 3 (14.7%)-MnO(7.5%) slag at 1500 • C and at oxygen partial pressure 2.75 × 10 −10 atm.…”
Section: Distributions Of Metals Between Copper Alloy and Slagsupporting
confidence: 60%
“…The behavior of manganese in CaO-SiO 2 -FeO-MgO-MnO slag-molten iron system at oxygen partial pressure 2.7 × 10 −12 atm was investigated by Jung et al [26]. The results showed that the equilibrium distribution coefficient of Mn between slag and iron increases with increasing FeO concentration and decreases with increasing basicity.…”
Section: Contextmentioning
confidence: 99%
“…3, it is indicated that the distribution of manganese reached equilibrium in 8 h and that equilibrium Fe t O content showed a steady value after 12 h. Therefore, 12 h was used for the equilibrium among liquid silver, solid iron and slag under a CO/CO 2 gas mixture. 12) at the same oxygen partial pressure. This is thought to be due to the effect of MgO on the activity of Fe t O.…”
Section: Determination Of Equilibration Timementioning
confidence: 98%
“…Thus, the information about the Fe t O activity in magnesiowustite is of great importance because the Fe t O activity in magnesiowustite and liquid slag is identical in case the magnesiowustite is the actual saturation phase in equilibrium with liquid slag. The current authors have previously investigated the thermodynamic behaviors of manganese oxide in the CaO-SiO 2 -Fe t O-Al 2 O 3 -MnOMgO sat 13) by equilibrating the liquid slag with liquid silver and solid iron in a MgO crucible. And they also did the similar research for CaO-SiO 2 -Fe t O-MnO 14) slags in equilibrium with liquid silver in a Fe crucible.…”
Section: Measurement Of Fe T O Activitymentioning
confidence: 99%